GIVING EXCLUSIVE ASI WITH THE EVENT OF DIARRHEA IN THE BABY 6 MONTHS - 2 YEARS - Ely Tjahjani (Jurnal Kebidanan Akademi Kebidanan Griya Husada Surabaya, 2018)
Diarrhea is more frequent defecation with a more runny consistency. Based on the results of the secondary data survey at BPS Ny. Ayu, the incidence of diarrhea in 2016 is still high from the target of 21.36%. Diarrhea can be caused because babies are not given exclusive breastfeeding, if the incidence of diarrhea is not treated, dehydration will occur and have a bad impact on the baby. Therefore this problem is deemed necessary to do research that aims to determine the relationship between exclusive breastfeeding and the incidence of diarrhea in BPS Ny. Ayu. Method: This study uses analytic design using a cross sectional design. Sampling is done by probability sampling with sistematic random sampling technique with a population of all infants aged 6 months - 2 years as many as 628 people and a total sample of 199 people. Secondary data collection from child registers. The results of the study were made frequency tables, cross tabulations and analysis by chi-square test with ? = 0.05. Results: Infants who were not given exclusive breastfeeding were 53.77%, and infants suffering from diarrhea were 50.25%. Based on the results of the chi-square test on exclusive ASI obtained ?2 Calculate> >2table which is 6.8> 3.84 so that H0 is rejected. Discussion: From the results of the study concluded that there is a relationship between exclusive breastfeeding and the incidence of diarrhea. Therefore to reduce the incidence of diarrhea, health workers must provide IEC and counseling on the importance of exclusive breastfeeding and things that might occur if not given exclusive breastfeeding, in order to create healthy babies.